theoretical assessment of the relations between innovation and businesses strategies with social impact (Sustainability in Debate, 2016)
This work seeks to explain theoretically the relationship between innovation and business strategies that have social impact. This theoretical study adopts an exploratory and qualitative approach, including bibliographic research in books and articles that deal with the pertinent topics. We found that the knowledge needed for innovation is spread more easily in environments in which there is freedom, encouragement of personal development, and creativity. The adoption of a culture that favors innovation generates several kinds of impacts in the organizational environment, especially in relation to issues of business that have a social impact. Both through the initiative of entrepreneurs and by organizational action, social innovation acquires its own features and contours, which are distinct from traditional innovation strategies. As a consequence, innovation must be present in businesses with social impact, in order to reach uncommon solutions that are not present in traditional businesses.